CLE40 Signaling Regulates Root Stem Cell Fate. Issue 4 (5th December 2019) - Berckmans, Barbara; Kirschner, Gwendolyn; Gerlitz, Nadja; Stadler, Ruth; Simon, Rüdiger
Abstract : Columella stem cell fate is controlled by factors acting independently of WUSCHEL RELATED HOMEOBOX 5 and the main role of the CLAVATA3/ESR-RELATED 40 peptide is the regulation of quiescent center activity and position. Abstract: The quiescent center (QC) of the Arabidopsis ( Arabidopsis thaliana ) root meristem acts as an organizer that promotes stem cell fate in adjacent cells and patterns the surrounding stem cell niche. The stem cells distal from the QC, the columella stem cells (CSCs), are maintained in an undifferentiated state by the QC-expressed transcription factor WUSCHEL RELATED HOMEOBOX5 (WOX5) and give rise to the columella cells. Differentiated columella cells provide a feedback signal via secretion of the peptide CLAVATA3/ESR-RELATED40 (CLE40), which acts through the receptor kinases ARABIDOPSIS CRINKLY4 (ACR4) and CLAVATA1 (CLV1) to control WOX5 expression. Previously, it was proposed that WOX5 protein movement from the QC into CSCs is required for CSC maintenance, and that the CLE40/CLV1/ACR4 signaling module restricts WOX5 mobility or function. Here, these assumptions were tested by exploring the function of CLE40/CLV1/ACR4 in CSC maintenance. However, no role for CLE40/CLV1/ACR4 in constricting the mobility of WOX5 or other fluorescent test proteins was identified. Furthermore, in contrast to previous observations, WOX5 mobility was not required to inhibit CSC differentiation. We propose that WOX5 acts mainly in the QC, where other short-range signals are generated that not only inhibit differentiation but also promote stem cell division in adjacent cells. Therefore, the main function of columella-derived CLE40 signal is to position the QC at a defined distance from the root tip by repressing QC-specific gene expression via the ACR4/CLV1 receptors in the distal domain and promoting WOX5 expression via the CLV2 receptor in the proximal meristem.